Impact of TNF inhibitors on inflammation-associated cognitive dysfunction in patients with rheumatoid arthritis: a prospective analysis - Natalia Mena-Vázquez; Natalia Mena-Vázquez; Fernando Ortiz-Márquez; Fernando Ortiz-Márquez; Fernando Ortiz-Márquez; Teresa Ramirez-García; Teresa Ramirez-García; Celia Gillis-Onieva; Pablo Cabezudo-García; Pablo Cabezudo-García; Aimara García-Studer; Aimara García-Studer; et al. (Frontiers in Medicine)
ObjectivesTo evaluate cognitive improvement in patients with rheumatoid arthritis (RA) after 6 months of treatment with tumor necrosis factor (TNF) inhibitors, analyze associated factors, and determine the percentage of patients achieving cognitive improvement.MethodsThis was a single-center prospective observational study conducted over 12 months on 70 RA patients initiating their first biologic disease-modifying antirheumatic drug (bDMARD) with a TNF inhibitor. Cognitive function was assessed at baseline and after 6 months using validated neuropsychological tests, including the Montreal Cognitive Assessment (MoCA) for global cognitive function, the digit span forward and backward tests for attention and working memory, and the Stroop-W, Stroop-C, and Stroop-CW tests for executive function and processing speed. Patient-reported outcomes were assessed using the Hospital Anxiety and Depression Scale (HADS) and the Quality of Life-Rheumatoid Arthritis Scale-II (QOL-RA II). Clinical variables, disease activity measured by the 28-joint Disease Activity Score based on C-reactive protein (DAS28-CRP), inflammatory markers including C-reactive protein (CRP) and erythrocyte sedimentation rate (ESR), and patient-reported outcomes were recorded. Associations with average CRP and Health Assessment Questionnaire (HAQ) scores were analyzed throughout the follow-up period. Cognitive improvement was defined as a ≥20% increase in MoCA test scores. Logistic regression was performed to identify factors associated with improvement.ResultsA total of 70 patients (mean age, 56.2 years; 81.4% female) were included. After 6 months, patients showed significant cognitive improvement in a validated questionnaire, namely, the Montreal Cognitive Assessment (MoCA test 23.1 ± 3.6 to 24.1 ± 3.3; p = 0.001), particularly in the executive and memory domains. Significant improvements were also observed in the digit span forward test (p = 0.003), digit span backward test (p = 0.021), Stroop-W test (p = 0.040), Stroop-C test (p = 0.014), and Stroop-CW test (p = 0.035). Improvements in the MoCA were associated with educational level (B = 2.628; p < 0.001), average CRP (B = −0.154; p = 0.002), and average HAQ (B = −0.303; p = 0.022). Similar associations were found for the other tests.ConclusionTNF inhibitor therapy in RA patients is associated with significant cognitive improvement, particularly in executive function and memory. These findings highlight the potential cognitive benefits of effective RA treatment and underscore the importance of addressing modifiable risk factors to enhance patient quality of life.